Patient Selection and Outcome of Hepatectomy for Noncolorectal Non-Neuroendocrine Liver Metastases - Abdalla, Eddie (2007)
Improved patient selection, introduction of more effective systemic treatments including targeted biologic and combined therapies, and the low morbidity and mortality rates of hepatobiliary surgery in centers of excellence are likely to provide continued improvements in outcomes for patients with noncolorectal non-neuroendocrine liver metastases. Further advances in treatment may emerge from better understanding of the underlying tumor biology for each cancer type and application of individualized care to each patien